PEMBENTUKAN DAN PERKEMBANGAN TASAWUF FALSAFI - Lusinta Rehna Ginting; Mely Nadia (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2021)
In the beginning, Sufism and philosophy were fused, so the two had a very close relationship. Of course, in an effort to reach the knowledge of God, it takes unusual thinking and is able to penetrate the spaces of physics. But lately many consider the two as contradictory things. In simple terms, Sufism is defined as the lifestyle of a Sufi which mostly leads to the purification of the soul in order to be closer to God. This paper is qualitative, with a library research approach. Philosophical Sufism began to develop since the 6th and 7th centuries Hijri. In Indonesia, philosophical Sufism was popularized by several well-known Sufi figures, for the Sumatra region philosophical Sufism was disseminated by Hamzah al-Fansuri, Syamsuddin al-Sumatrani, Abd al-Ra'uf al-Singkili. As for the Java region, the figure who is famous for popularizing philosophical Sufism is Shaykh Siti Jenar. The figures and doctrines of philosophical Sufism are: Al-Hallaj with the concept of Hulul, Suhrawardi with the concept of Illumination, Ibn 'Arabi with the concept of Wahdah Al-Wujud, and Abu Yazid Al-Bustami with the concept of Fana' and Baqo'.